Role of vascular endothelial cell growth factor in Ovarian Hyperstimulation Syndrome. - Levin, E R (1998)
Controlled ovarian hyperstimulation with gonadotropins is followed by Ovarian Hyperstimulation Syndrome (OHSS) in some women. An unidentified capillary permeability factor from the ovary has been implicated, and vascular endothelial cell growth/permeability factor (VEGF) is a candidate protein. Follicular fluids (FF) from 80 women who received hormonal induction for infertility were studied. FFs were grouped according to oocyte production, from group I (0-7 oocytes) through group IV (23-31 oocytes). Group IV was comprised of four women with the most severe symptoms of OHSS. Endothelial cell (EC) permeability induced by the individual FF was highly correlated to oocytes produced (r2 = 0.73, P < 0.001). Group IV FF stimulated a 63+/-4% greater permeability than FF from group I patients (P < 0. 01), reversed 98% by anti-VEGF antibody. Group IV fluids contained the VEGF165 isoform and significantly greater concentrations of VEGF as compared with group I (1,105+/-87 pg/ml vs. 353+/-28 pg/ml, P < 0. 05). Significant cytoskeletal rearrangement of F-actin into stress fibers and a destruction of ZO-1 tight junction protein alignment was caused by group IV FF, mediated in part by nitric oxide. These mechanisms, which lead to increased EC permeability, were reversed by the VEGF antibody. Our results indicate that VEGF is the FF factor responsible for increased vascular permeability, thereby contributing to the pathogenesis of OHSS.